RCAT reflects symptom control and quality of life in allergic rhinoconjunctivitis patients. Issue 5 (29th December 2017) - Liedtke, J.‐P.; Mandl, A.; Köther, J.; Chwieralski, J.; Shah‐Hosseini, K.; Raskopf, E.; Pieper‐Fürst, U.; Allekotte, S.; Mösges, R.
Abstract: Background: The Global Allergy and Asthma European Network (GA 2 LEN) Taskforce has requested more data on correlations between various patient‐reported outcomes (PROs) in clinical trials on allergy. We compared three tools—the Rhinitis Control Assessment Test (RCAT), Rhinoconjunctivitis Quality of Life Questionnaire (RQLQ) and Rhinitis Total Symptom Score (RTSS)—to determine whether the RCAT alone is a sufficient primary outcome parameter in clinical trials on allergic rhinoconjunctivitis. Methods: In two double‐blind, placebo‐controlled immunotherapy studies, 33 patients allergic to grass pollen and 94 to birch pollen completed two questionnaires (RCAT and RQLQ) and kept their own symptom diary from which the RTSS was calculated. Results: Upon comparing RCAT and RQLQ results, we found strong correlations of r = −0.871 for grass pollen–allergic patients and r = −0.795 for birch pollen–allergic patients. The comparison between RCAT and RTSS results showed a strong correlation of r = −0.811 (grass pollen–allergic patients) and a moderate correlation of r = −0.539 (birch pollen–allergic patients). In the RCAT, 69.7% of grass pollen–allergic patients and 45.7% of birch pollen–allergic patients receiving guideline‐concordant therapy were regarded as having insufficiently controlled symptoms. Conclusion: The strong correlations suggest that the RCAT alone is equivalent to the RQLQ with respect to patients' symptom control and quality of life. Patients with uncontrolled symptoms can be identified using the RCAT. Hence, the physician can decide whether symptomatic therapy can be intensified or allergy immunotherapy should be administered.